Determinants of the household electricity consumption efficiency of an ageing population: Evidence for the EU-28. (December 2020) - Pais-Magalhaes, Vera; Moutinho, Victor; Robaina, Margarita
Abstract: This paper explores the determinants of household electricity consumption efficiency of an ageing population. The analysis is pursued for the 28 member states of the European Union between 2005 and 2016. These determinants are evaluated through the employment of the econometric method Fractional Regression Model. Results indicate that the share of renewables in heating and cooling, the government expenditures in housing and community and the housing cost burden below 60% for people aged 65 and over, are the main drivers that impulse the efficiency levels positively. On the other hand, the old age dependency ratio, and the housing cost burden above 60% for people aged 65 and over, affect the efficiency levels negatively. The main contribution of the study is to underline the relevance of the socio-economic household characteristics of an ageing population strata in explaining the residential electricity consumption efficiency.